Система имиджеобразующих факторов современного украинского банка - Погребняк, А. (Социология: теория, методы, маркетинг, 1999)
In sociological research context, the author analyzes the image creating factors of the most significance for client while choosing a bank. The following image creating functions is picked out to be the main: related to prestige, information, barrier, reminding, pre-advertising. Special attention is paid to the role of mass media, public relations and governmental policy towards development of positive images of banks.